المهارات الحياتية اللازمة للطلبة بمرحلة التعليم الأساسي في ضوء متغيرات العصر - Abdul Hakim, Abdullah; Cisse, Ahanadou (2017)
The study aimed at determining the most important life skills required for students in basic education in the light of the variables of the age. The study found that the most important life skills required for students in basic education are: writing skills, reading skills, problem solving skills, innovation and creativity skills, Self-management. The study recommended that learners should acquire these skills and train them through intensifying classroom and non-classroom activities.